2021
DOI: 10.1093/jae/ejab027
|View full text |Cite
|
Sign up to set email alerts
|

Income Distribution and the Potential of Redistributive Systems in Africa: A Decomposition Approach

Abstract: Redistributive systems in Africa are still in their infancy but are expanding in order to finance increasing public spending. This paper aims at characterising the redistributive potential of six African countries: Ghana, Zambia, Mozambique, Tanzania, Ethiopia and South Africa. These countries show contrasted situations in terms of income distribution. We assess the role of tax-benefit systems to explain these differences. Using newly developed tax-benefit microsimulations for all six countries, we produce cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…These poverty effects are often negative also after accounting for benefits and pensions. At large, the findings are in line with earlier research highlighting the limited effectiveness of tax-benefits systems in sub-Saharan Africa to redistribute resources and reduce poverty (e.g., Inchauste and Lustig 2017;Brown et al 2018;Bargain et al 2022;Gasior et al 2022a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These poverty effects are often negative also after accounting for benefits and pensions. At large, the findings are in line with earlier research highlighting the limited effectiveness of tax-benefits systems in sub-Saharan Africa to redistribute resources and reduce poverty (e.g., Inchauste and Lustig 2017;Brown et al 2018;Bargain et al 2022;Gasior et al 2022a).…”
Section: Discussionsupporting
confidence: 89%
“…The current paper expands previous comparative work assessing the performance of tax-benefit systems in the Global South based on SOUTHMOD models (see Bargain et al 2022;Gasior et al 2022a;Lastunen et al 2023). Our work extends the scope of these papers by incorporating additional countries, made possible by new microsimulation models, and by examining a number of outcomes in greater detail.…”
Section: Introductionmentioning
confidence: 70%
“…This research contributes to the literature by offering the most extensive cross-country comparative study for Africa analysing the distributional impact of tax-benefit policies during the pandemic. It highlights the limited role of automatic stabilizers in African countries, contributing to the limited evidence on how these countries fare in terms of the power of their redistributive systems, in general and during shocks (Bargain et al 2022;Devarajan et al 2013;Gasior et al 2021). Additionally, the study examines the effectiveness of discretionary tax-benefit measures and related changes in alleviating shocks to households, and it provides estimates of changes in poverty and inequality during the pandemic in the selected countries.…”
Section: Introductionmentioning
confidence: 99%
“…Gasior et al (2018) and Bargain et al (2021) examine the distributional role of tax and benefit systems. Bargain et al (2021) assess the distributional effects by applying the tax and benefit system of the most (least) redistributive country to the population of the remaining countries. Lastunen et al (2021) look at cushioning effects of tax and benefits for poverty and inequality in Africa amid the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Based on World Bank (2020a) ranking, the six countries cluster into low-income (Ethiopia, Mozambique, and Uganda), lowermiddle-income (Tanzania and Zambia) and upper-middle-income (South Africa) economies. Gasior et al (2018) and Bargain et al (2021) demonstrated that direct tax is more redistributive in Ethiopia, South Africa, and Tanzania and less redistributive in Mozambique and Zambia. Therefore, our study attempts to assess the extent to which the fiscal drag size varies across the level of economic development and tax policy arrangement highlighting the impact on the worst-off individuals previously exempted and then dragged into taxable income threshold.…”
mentioning
confidence: 99%